Tight-coupled Microstrip Hairpin Bandpass Filter - Ramdedović, Amel; Imeci, Sehabeddin Taha (Elsevier, 2023)
The paper depicts a microstrip hairpin bandpass filter design, simulation, fabrication and test. The proposed microstrip filter's design is comprised of five hairpin structures separated by a tenth of a mm distance for which various parametric studies have been conducted. The simplicity of design provides inexpensive and undemanding filter. The filter is fabricated with suitable parametric results. The design is based on Chebyshev's values for the prototype, with N (the order of filter) number being equivalent to five. The final fabricated version of the project is based upon FR4 dielectric substrate with the input return loss being below-10 dB and insertion loss above-2 dB. Approximate values of the input reflection coefficient and insertion loss are-33.34 dB and-1.72 dB respectively. Furthermore, the frequency range for the proposed geometry is between approximately 2.6 GHz and 3.6 GHz. The proposed filter is fabricated and the results measured in real life are highly correlated to the results simulated in the software. The proposed microstrip hairpin bandpass filter can be utilized in wireless internet access and communication.
Keywords: Microstrip; Bandpass filter; Sonnet Suites Software; FR4; Chebyshev’s values